The Benefits of E-SAR (Adolescent Anemia Screening) in Efforts to Free Adolescents from Anemia - Julianawati, Tinta; Fariningsih, Erika; Ayuandini, Ayuandini; Fransiska, Fransiska (Edumedia Solution, 2026)
The problem of anemia among adolescent girls in Indonesia remains a significant challenge due to its high prevalence, primarily due to unbalanced nutritional intake, low consumption of iron-fortified tablets (TTD), and menstrual patterns that increase the risk of iron loss. Currently, in island regions, particularly at the Healthy Teenagers Integrated Health Post (Posyandu), anemia screening is not yet digitally based, so examinations, recording, and reporting of anemia status are still carried out manually without the use of digital technology. This process usually relies on simple examination tools, recording in a register, and reporting using conventional methods, making it prone to delays, errors, and data loss. Therefore, this community service program, which includes outreach on the importance of early anemia detection and the development of guidelines for using the anemia screening website for adolescents, and mentoring cadres and adolescents in website usage, can reduce the incidence of anemia in adolescents. Thus, this program is expected to increase the independence of Posyandu in monitoring adolescent health while strengthening sustainable anemia prevention efforts.